The media representation of female healthcare professionals in Spain and China: An analysis of themes, attributes and stereotypes in the press - Zhang, Xingyue; Chaparro-Domínguez, María-Ángeles; Segado-Boj, Francisco (Revista Española de Comunicación en Salud, 2026)
Introduction: Female healthcare workers form the backbone of the health system and play a vital role in the population’s well-being. However, their media visibility remains limited. The way the media report on them influences the social and professional recognition they receive. Objectives: This study aims to analyze the media portrayal of female healthcare workers in major Spanish and Chinese newspapers. Methodology: A quantitative content analysis was conducted of 1,232 news articles published over a seven-year period in El País and ABC (Spain), and in People’s Daily and South China Morning Post (China). Results: Female healthcare workers are associated more frequently than men with maternal, physical, and emotional attributes. By contrast, the Chinese press places emphasis on their physical attributes, whereas the Spanish press more frequently highlights their professional knowledge. Conclusion: Gender stereotypes are deeply embedded in the way Spanish and Chinese newspapers portray female healthcare personnel, and these stereotypes continue to shape both their visibility and the recognition of their professional competencies.
Keywords: media coverage; press; newspapers; female; workers; stereotypes; Spain; China